Ethyl Pyruvate Reduces Systemic Leukocyte Activation via Caspase-1 and NF-κB After Blunt Chest Trauma and Haemorrhagic Shock - Scott Dieteren; Scott Dieteren; Niklas Franz; Kernt Köhler; Aleksander Nowak; Sabrina Ehnert; Alexey Surov; Marcus Krüger; Ingo Marzi; Nils Wagner; Borna Relja (Frontiers in Medicine, 2020)
Background: Blunt chest (thoracic) trauma (TxT) and haemorrhagic shock with subsequent resuscitation (H/R) induce strong systemic and local inflammatory response, which is closely associated with apoptotic cell loss and subsequently impaired organ function. The underlying mechanisms are not completely understood, therefore, the treatment of patients suffering from TxT+H/R is challenging. In our recent studies, we have demonstrated local anti-inflammatory effects of ethyl pyruvate (EtP) in lung and liver after TxT+H/R. Here, the therapeutic potential of a reperfusion regime with EtP on the early post-traumatic systemic inflammatory response and apoptotic changes after TxT followed by H/R were investigated.Methods: Female Lewis rats underwent TxT followed by haemorrhagic shock (60 min). Resuscitation was performed with own blood transfusion and either lactated Ringers solution (LR) or LR supplemented with EtP (50 mg/kg). Sham group underwent the surgical procedures. After 2 h blood as well as lung and liver tissues were obtained for analyses. Systemic activation of neutrophils (expression of CD11b and CD62L), leukocyte phagocytosis, apoptosis (caspase-3/7 activation), pyroptosis (caspase-1 activation) and NF-κB p65 activity were assessed. p < 0.05 was considered significant.Results: TxT+H/R-induced systemic activation of neutrophils (increased CD11b and reduced CD62L expression) was significantly reduced by EtP. Trauma-induced delayed neutrophil apoptosis was further reduced by EtP reperfusion but remained unaltered in monocytes. Reperfusion with EtP significantly increased the phagocytizing capacity of granulocytes. Trauma-induced inflammasome activation, which was observed in monocytes and not in neutrophils, was significantly reduced by EtP in both cell entities. NF-κB p65 activation, which was increased in neutrophils and monocytes was significantly decreased in monocytes.Conclusion: TxT+H/R-induced systemic activation of both neutrophils and monocytes concomitant with increased systemic inflammation was reduced by a reperfusion with EtP and was associated with a down-regulation of NF-κB p65 activation.